Risk factors of Post Extubation Dysphagia (PED) among critically ill patients in Intensive Care Unit / Nuraeiniza Ismail - Nuraeiniza, Ismail (2019)
Objective: Post-extubation dysphagia (PED) is a common disorder that occurs following extubation. The prevalence of post-extubation dysphagia varies significantly from 3% to 62% to even 84% of adult patients who undergo prolonged mechanical ventilation due to the different diagnostic criteria and also population characteristic. This study will provide information on predictive risk factors in critically ill patient that are contributing to the development of PED. Methods: A prospective observational study over the period of 4 months from October 2018 to January 2019 were carried out in intensive care unit (ICU) at the University Malaya Medical Centre (UMMC). Fifty seven critically ill patients aged 18 years and above who were mechanically ventilated with endotracheal intubation for any duration were recruited in this study. Patient’s demographic and ICU related data were collected daily until maximum 14 days. Within 48hrs post extubation, patients were asked to perform the Repetitive Saliva Swallowing test (RSST) and completed the Sydney Swallowing Questionnaire (SSQ). These evaluations were repeated at day 7 post extubation. Results: The prevalence of PED in this study was 35.1%. Repeated evaluation at day 7 post extubation showed 94.3% of patients were at low risk of PED. Incremental factors associated with an increased risk for PED include higher SAPS II score (p=0.026), ischemic heart disease (p=0.027) and chronic obstructive pulmonary disease (p=0.031). Age and duration of mechanical ventilation did not increase the risk of PED. Conclusion: In this prospective study, patients with higher SAPS II score, comorbidities ischemic heart disease and chronic obstructive pulmonary disease were associated with higher risk of PED. Majority of the patients were able to recover from PED by day 7 post extubation.